Sustainable ESG practices and smart manufacturing adoption readiness for SME operational agility: The conditional mediating role of financial access - Alexandra S. Kang; Swee Loke Hew (Sustainable Futures)
As global sustainability pressures intensify and technological change accelerates, SMEs face a growing urgency to enhance their agility and resilience. This study investigates the influence of sustainable practices in environmental (SEP), social (SSP), and governance (SGP) on SME operational agility (OA). It explores the mediating role of smart manufacturing adoption readiness (SMAR) and the moderating effect of access to finance (AF) within this relationship. A conditional mediation model was developed and tested using partial least squares structural equation modelling (PLS-SEM) on data from 117 Malaysian manufacturing SMEs. Results show that SEP, SSP, and SGP significantly enhance SMAR, explaining 54.4 % of its variance. While SMAR alone does not directly impact OA, it has a significant indirect effect when conditioned on AF. The conditional mediation pathways from SEP, SSP, and SGP to OA through SMAR are supported, with AF strengthening these effects. In addition, AF significantly moderates the relationship between SMAR and OA. These findings highlight the strategic value of integrating sustainable ESG practices, SMAR, and AF to enhance OA among SMEs to remain competitive in a volatile and sustainability-driven global landscape.